(untitled) (Research, Society and Development, 2021)
The objective was to evaluate the inclusion of a combination of carvacrol + cinnamaldehyde and carvacrol + cinnamaldehyde + yeasts on performance, organ yield, intestinal morphometry and serum biochemical parameters in broilers. 360 female broiler chicks of the COBB 500 strain were used, distributed on the first day of age in a completely randomized experimental design, composed of four treatments: negative control, flavomycin, carvacrol + cinnamaldehyde and carvacrol + cinnamaldehyde + yeasts, consisting of six replicates with 15 animals each. The phytogenic + yeast blend comprised the use of 75% yeast and 25% herbal extracts, in their composition, in the 1-21 day phase, 50% yeast and 50% herbal extracts in 22-35 days and 25% yeast and 75% herbal extracts in 35-42 days. There was a reduction (P<0.05) in live weight and weight gain in birds supplemented with carvacrol + cinnamaldehyde, and mortality was lower (P<0.05) in birds in the group with Flavomycin. There were no changes (P> 0.05) in the organ yield and the height of the intestinal villi (P> 0.05), however, the crypt depth was greater (P<0.05) in birds supplemented with Flavomycin. A higher villus / crypt ratio (P<0.05) was found in chickens supplemented with phytogenics + yeasts, compared to birds that received flavomycin. There were no differences (P>0.05) between the serum biochemical parameters evaluated. The inclusion of carvacrol and cinnamaldehyde + yeasts can replace antibiotics in the feed of broilers, guaranteeing adequate productive performance and without compromising organs, intestinal morphometry and serum biochemistry.